Caring and Sharing to Improve Students’ Well-Being in Distance Learning - Vica Ananta Kusuma; Binti Muflikah; Isma Dwi Fiani (Universitas Pahlawan Tuanku Tambusai, 2023)
Students’ well-being has become a recent concern in education. Many related literatures mentioned that well-being is one of the significant factors in determining students’ success. However, many distance education students experience loneliness and alienation because of lacking social presence and social connectedness. Those problems resulted in a low level of well-being. To deal with the problem, the department carries out Caring and Sharing regularly. The program includes an e-lecture, webinar, greeting from the department, and alumni’s story. The present research aims to explore the students’ perception of Caring and Sharing in improving well-being. To achieve the purpose of the study, a narrative inquiry is employed. Three students from English Literature Department who joined Caring and Sharing were interviewed to know their perception and experience in the program. The finding shows that the students have positive reactions regarding Caring and Sharing and they agree that the program helps improve their well-being. It builds the students’ sense of belonging, confidence, and motivation to study. Moreover, it also identifies aspects influencing their well-being in distance learning. The limitations of the findings are discussed for future research.